2021
DOI: 10.1093/pubmed/fdaa279
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic factors and the probability of death by Covid-19 in Brazil

Abstract: Background To design better measures to contain the Covid-19 epidemics, it is relevant to know whether socioeconomic factors are associated with a higher risk of death by Covid-19. This work estimates the effects of individual socioeconomic characteristics on the risk of death by Covid-19. Methods Logistic models were estimated to assess the effect of socioeconomic characteristics (income, race/ethnicity, schooling, occupatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 9 publications
2
21
0
6
Order By: Relevance
“…Recent work by Verma et al [63] demonstrated that COVID-19 case count was significantly higher in lower-income neighborhoods within the United States. Similar findings have been reported in other parts of the world [39,9], all while controlling for external factors and environmental variables. Few studies have explored the combination of visit duration and global pandemics but those that have are typically focused on the epidemiological facet.…”
Section: Related Worksupporting
confidence: 88%
“…Recent work by Verma et al [63] demonstrated that COVID-19 case count was significantly higher in lower-income neighborhoods within the United States. Similar findings have been reported in other parts of the world [39,9], all while controlling for external factors and environmental variables. Few studies have explored the combination of visit duration and global pandemics but those that have are typically focused on the epidemiological facet.…”
Section: Related Worksupporting
confidence: 88%
“…Data constraints limited the numbers of factors we were able to explore – for example, despite evidence ( Kiti et al, 2014 ) suggesting that contact patterns differ across rural and urban settings, only three studies ( Kiti et al, 2014 ; le Polain de Waroux et al, 2018b ; Neal et al, 2020 ) contained information from both rural and urban sites, allowing classification. Similarly, we were unable to examine the impact of socioeconomic factors such as household wealth, despite experiences with COVID-19 having highlighted strong socioeconomic disparities in both transmission and burden of disease ( De Negri et al, 2021 ; Routledge et al, 2021 ; Ward et al, 2021 ; Winskill et al, 2020 ) and previous work suggesting that poorer individuals are less likely to be employed in occupations amenable to remote working ( Loayza, 2020 ). A lack of suitably detailed information in the studies conducted precludes analysis of these factors but highlights the importance of incorporating economic questions into future contact surveys, such as household wealth and house square footage.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, we were unable to examine the impact of socioeconomic factors such as household wealth, despite experiences with COVID-19 having highlighted strong socio-economic disparities in both transmission and burden of disease (De Negri et al, 2021;Routledge et al, 2021;Ward et al, 2021;Winskill et al, 2020) and previous work suggesting that poorer individuals are less likely to be employed in occupations amenable to remote working (Loayza, 2020). A lack of suitably detailed information in the studies conducted precludes analysis of these factors but highlights the importance of incorporating economic questions into future contact surveys, such as household wealth and house square footage.…”
Section: Discussionmentioning
confidence: 99%